2019
DOI: 10.1007/s42452-019-0660-8
|View full text |Cite
|
Sign up to set email alerts
|

Technological, applications, and characteristics of edible films and coatings: a review

Abstract: In the last 2 decades, food packaging and packaging industry have received considerable attention from those who interested in manufacturing edible films and biodegradable packaging materials. The interest in whey proteins has increased because of their environmental benefits, availability in large quantities as residues, non-toxicity, low price, high nutritional values, and suitability for the packaging and protecting foods from damage. The purpose of this work is to highlight and review the importance of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 63 publications
0
49
0
Order By: Relevance
“…Different investigations have showed that adding probiotic bacteria into cheeses decreases the flavor acceptability of cheese compared to control cheeses. The proteolytic enzymes (which are originated by lactic acid bacteria) break down the milk proteins to produce small peptides and amino acids [67,68]. It has been found that the addition of different strains of probiotics into Cheddar cheese and Ras cheese resulted in decreasing the flavor of these cheeses [7,54].…”
Section: The Sensory Characteristics Of Probiotic and Nonprobiotic Chmentioning
confidence: 99%
“…Different investigations have showed that adding probiotic bacteria into cheeses decreases the flavor acceptability of cheese compared to control cheeses. The proteolytic enzymes (which are originated by lactic acid bacteria) break down the milk proteins to produce small peptides and amino acids [67,68]. It has been found that the addition of different strains of probiotics into Cheddar cheese and Ras cheese resulted in decreasing the flavor of these cheeses [7,54].…”
Section: The Sensory Characteristics Of Probiotic and Nonprobiotic Chmentioning
confidence: 99%
“…These films and coatings are considered a barrier in order to prevent the loss of foods’ volatile flavor compounds and to protect the product from microorganisms’ damage. Since they can be easily incorporated with natural substances (antioxidants, additives, preservatives, dyes), alginate films and nanocapsules help to improve the product’s appearance and make it more attractive for a consumer [ 33 ]. Furthermore, alginate can be used to preserve the qualities and prolong the shelf life of foods, especially for the controlled release of incorporated compounds.…”
Section: Sodium Alginate In the Food Industrymentioning
confidence: 99%
“…Bio-based polymers are defined as polymeric materials produced from renewable raw materials (which may or may not be biodegradable). In addition to other features, special properties such as biodegradability, regenerability, relatively low-cost development, abundance in nature, non-toxicity, and biocompatibility have made them intensively used to obtain new innovative materials [10][11][12]. By 2011, the production of bio-based polymers had reached the threshold of 3.2 billion tonnes, and it is expected that after 2020 it will reach the threshold of 12 billion tonnes [13].…”
Section: Films and Coatings Used In The Food Industrymentioning
confidence: 99%